2019
DOI: 10.2519/jospt.2019.0611
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Quadriceps Tendinopathy and Patellar Tendinopathy: Semantics or Significant?

Abstract: Jumper's knee is not synonymous with patellar tendinopathy. The term includes patellar tendinopathy and quadriceps tendinopathy. Although the patellar and quadriceps tendons work in tandem as part of the extensor mechanism of the knee, they have distinct anatomy and functional roles. As a result, there are probable differences in risk factors, etiology, and response to treatment. It is time to clinically separate patellar tendinopathy and quadriceps tendinopathy and design more specific rehabilitation programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…This is a less common tendinopathy then patellar tendinopathy; it affects the cranial part of the patella. It is considered as part of the jumper knee syndrome and usually it is not differentiated from the patellar tendinopathy, while, as highlighted by Sprague et al, the two tendons have different structures and different treatments [ 44 ]. Quadriceps tendinopathy, due to its low prevalence, has rarely been studied with ultrasound [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is a less common tendinopathy then patellar tendinopathy; it affects the cranial part of the patella. It is considered as part of the jumper knee syndrome and usually it is not differentiated from the patellar tendinopathy, while, as highlighted by Sprague et al, the two tendons have different structures and different treatments [ 44 ]. Quadriceps tendinopathy, due to its low prevalence, has rarely been studied with ultrasound [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Higher levels of kinesiophobia have been associated with worse recovery of lower extremity function in Achilles tendinopathy [ 27 ]. Additionally, in pilot studies, we found that the majority of patients with patellar tendinopathy have clinically meaningful levels of kinesiophobia [ 28 ]. Scores range from 17 to 68 points, with higher scores indicating a greater fear of movement and re-injury.…”
Section: Methodsmentioning
confidence: 99%
“…111,112 Tendon pathology ranges from acute tears to chronic degenerative overuse. 113,114 Treatment is largely determined by the specific tendons involved, location (intratendinous versus myotendinous), and timing (acute versus chronic). 115 In the setting of acute tears, treatment is aimed at promoting cellular proliferation and healing, whereas chronic tendinopathy is managed by targeting inflammatory mediators and inhibiting matrix-degrading proteinases to improve healing (Table 5).…”
Section: Tendon Pathology Brief Overviewmentioning
confidence: 99%